Respostas
respondido por:
0
Boa dia
Para esboçar a função
f(x)= x² - 2x + 5
f(-3) = 9 + 6 + 5 = 20
f(-2) = 4 + 4 + 5 = 13
f(-1) = 1 + 2 + 5 = 8
f(0) = 5
f(1) = 1 - 2 + 5 = 4
f(2) = 4 - 4 + 5 = 5
f(3) = 9 - 6 + 5 = 8
Para esboçar a função
f(x)= x² - 2x + 5
f(-3) = 9 + 6 + 5 = 20
f(-2) = 4 + 4 + 5 = 13
f(-1) = 1 + 2 + 5 = 8
f(0) = 5
f(1) = 1 - 2 + 5 = 4
f(2) = 4 - 4 + 5 = 5
f(3) = 9 - 6 + 5 = 8
Anexos:
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás